A strategic vision for Africa : the Kampala movement - Deng, Francis Mading, 1938- (Brookings Institution Press, 2002)
"As the cold war ended, Africa was a major battlefield in the ideological war between the United States and the Soviet Union. However, changing priorities in the United States and the dissolution of the USSR pushed Africa out of the spotlight and into obscurity. As globalization, development, and regional cooperation advanced in much of the world, Africa lingered in provincialism, poverty, and war. It received the attention of the world only when it was unavoidable, as in the Somali state collapse and Rwandan genocide in 1992 and 1994." "This book chronicles the efforts, made manifest in the Kampala Principles, of a determined group working to solve Africa's complex problems. In 1989 Olusegun Obasanjo, then Nigerian head of state and now the democratically elected president, organized the first of many forums that resulted in the Kampala Principles, a document providing a framework for workable political and economic development in Africa. Taking the Helsinki Document of 1975 as their model, participants in the several forums settled on seven key tenets geared toward the adoption of a new and comprehensive politico-economic regime on the continent. They also created a longer declaration of norms and principles."--Jacket